2015
DOI: 10.3920/wmj2014.1818
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of deoxynivalenol, zearalenone, and their respective modified analogues in milling fractions of naturally contaminated wheat grains

Abstract: Mycotoxins are among the most abundant contaminants in food and feed worldwide. Therefore, in the EU maximum levels are established, e.g. for the frequently occurring Fusarium toxins deoxynivalenol (DON) and zearalenone (ZEA). Additional to DON and ZEA, modified mycotoxins are present in naturally contaminated grain products contributing significantly to the exposure of humans and animals with mycotoxins. Up to now data on the spatial distribution of many (masked) mycotoxins in the kernels of wheat are missing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 23 publications
2
30
0
Order By: Relevance
“…Fewer previous studies have investigated the effects of milling on distribution of ZON. Where studied, the distribution of ZON was less variable than DON and was consistently higher in the bran and offal fractions and lower in white flour fractions (Schwake-Anduschus, et al, 2015;TrigoStockli, Deyoe, Satumbaga, & Pedersen, 1996;Zheng, et al, 2014) and no significant seasonal differences in the distribution of ZON were observed (Edwards, et al, 2011).…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Fewer previous studies have investigated the effects of milling on distribution of ZON. Where studied, the distribution of ZON was less variable than DON and was consistently higher in the bran and offal fractions and lower in white flour fractions (Schwake-Anduschus, et al, 2015;TrigoStockli, Deyoe, Satumbaga, & Pedersen, 1996;Zheng, et al, 2014) and no significant seasonal differences in the distribution of ZON were observed (Edwards, et al, 2011).…”
Section: Introductionmentioning
confidence: 85%
“…Studies in several countries, using a range of varieties and different mills have identified that after milling there is a lower proportion of DON within the white flour fractions and higher proportion in the bran and offal fractions. The impact of dry milling of wheat on deoxynivalenol was reviewed by (Cheli, Pinotti, Rossi, & Dell'Orto, 2013) and (Kushiro, 2008) and subsequently reported in more recent publications (Brera, et al, 2013;Fernandes, Barros, Santo, & Camara, 2015;Savi, et al, 2016;Schwake-Anduschus, et al, 2015;Tibola, Fernandes, Guarienti, & Nicolau, 2015;Zhang & Wang, 2014;Zheng, et al, 2014). Typical concentrations in white flour are 50-80% of the cleaned grain DON concentration.…”
Section: Introductionmentioning
confidence: 99%
“…Since mycotoxin contamination often concerns the outer layers of kernels, debranning can reduce DON contamination by 15 to 78% (Aureli and D'Egidio 2007;Rios et al 2009;Cheli et al 2010;Sovrani et al 2012). This leads to the conclusion that wheat bran is more contaminated with DON, ZEN and ENN B and B 1 than wheat flour (Vaclavikova et al 2013;Schwake-Anduschus et al 2015;Tibola et al 2015). Wheat bran was used at average levels of 6.8 ± 0.7% (mean ± SEM) in all 97 investigated fish feeds ( Fig.…”
Section: Estimation Of the Mycotoxin Contamination Levels And Their Imentioning
confidence: 98%
“…ZEN was found to be more concentrated in the fibre‐rich parts of grains. The efficiency of milling in reducing the contamination level is due to the removal of the fractions from further processing, which are more enriched with mycotoxins …”
Section: Detoxification/inactivation Of Mycotoxinsmentioning
confidence: 99%